ANALISIS PENYEBAB KETIDAKMAMPUAN ANGGOTA MEMBAYAR KREDIT PADA CU SEMANDANG JAYA DI DESA SEMANDANG KECAMATAN SIMPANG HULU KABUPATEN KETAPANG - Oka Wilisimindala; Khosmas Khosmas; Okianna Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe problem in this study is the cause of the inability of members to pay credit at the Semandang Jaya CU in Semandang Village, Simpang Hulu District, Ketapang Regency. This study uses a qualitative descriptive method in the form of field survey research, as for the conclusions that can be drawn after conducting direct field research so that it can be seen the cause of bad loans from the members, namely members of CU Sendang Jaya not taking advantage of loans that are not in accordance with the original purpose, there are members who borrow credit to open a business but the business that is managed does not run smoothly so there is no income to be able to pay the credit, there are also some members who have bad intentions so they deliberately take loans without returning the loan to CU Semandang Jaya. Meanwhile, from the CU side, CU employees are not careful in analyzing lending to members and there are still loans to members who do not meet the requirements due to family relationships. The largest credit ratio in the last five years in 2015 was 7.1% in 2016 at 5.5% in 2017 as compared to 5.5% in 2018 at 7.4% and in 2019 at 7.2% where this figure meet the maximum limit, namely the ratio of nonperforming loans reaching 5% which indicates the CU is not healthy. The largest credit ratio in 2018 was 7.4%.Keywords: inability to pay credit, bad credit, credit union